Paralelo entre O mulato de Aluísio de Azevedo e The house behind the cedars de Charles Chesnutt: preconceitos e contradições - Júnior, Orison Marden Bandeira de Melo (2007)
The present research proposes a comparative study between O Mulato, by Aluísio Azevedo and The House Behind the Cedars, by Charles Chesnutt, aiming at verifying some evidence of race prejudice in the voice of the novels narrators. Due to that, I first tried to analyze some scientific theories which have defended the inferiority of the black race and their portrayal through various stereotypes found not only in the novels which constitute the corpus of this study, but also in some prior to them. Furthermore, I examined some concepts from Comparative Literature which guided not only the comparison between the two frontier novels but also the use of notions from Science, History and Religion. Thus, I verified that both narratives were analogous in various aspects, among which I mention: (1) small and prejudiced cities; (2) the chronological time of the plots determined by historical events; (3) thirdperson omniscient and intrusive narrators; (5) afro-descendent heroes portrayed with physical and cultural characteristics of white heroes; (6) the end of the heroes by death, and (7) interracial relationship as the intriguing element of racial discrimination portrayed in the novels. Among the individual characteristics of each book, I pointed out (1) the angle of vision in the narratives, since the world depicted in O Mulato is the world of white people whereas the world in The House Behind the Cedars is the world of black people, and (2) the consciousness of black ancestry, which is not found in the main character of the Brazilian novel and is always present in the main character of the American novel. Finally, I tried to answer the research question by concluding that I believe that there is a contradiction in the voice of the narrator, who, although telling a plot whose ideological function is to fight against race prejudice, corroborates the racist scientific theories by describing secondary characters in the narratives stereotypically and afro-descendent heroes with physical and cultural characteristics of white heroes